Variables related to socialanxiety in adolescents: a multiple linear regression model - Samaniego, Antonio (2016)
The objective was to build a multiple regression model to investigate the relationship between social anxiety, anxiety sensitivity, trait anxiety and fear of negative evaluation, and to compare men and women. The research was quantitative, not experimental, correlational and cross-sectional. 689 adolescents between 14 and 19 years (M=16.45; SD=1.11) were evaluated, through the Social Anxiety Scale for Adolescents (SAS-A), the trait subscale of the Trait Anxiety Inventory-State (STAI), the Brief Fear of Negative Evaluation Scale (BFNE) and Anxiety Sensitivity Index-3 (ASI-3) were applied. Female gender showed higher mean in trait anxiety with small effect size (d=-.27). Correlations were positive from low to moderate. The higher partial and semipartial correlation was between SAS-A and ASI. A valid regression model and statistically significant was constructed and explained 41.2% of the variance of social anxiety (R2=.412) with large effect size.